SPE Unconventional Resources Conference 2014
DOI: 10.2118/169022-ms
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Enhanced Recovery in Unconventional Liquid Reservoirs using CO2: A Look Ahead to the Future of Unconventional EOR

Abstract: The poor rock quality and matrix permeability several orders of magnitude lower than conventional oil reservoirs observed in unconventional liquid reservoirs (ULR) presents many uncertainties on the storage capacity of the rock and the possibility of enhancing recovery. The technological advances in multiple stage hydraulic fracturing and horizontal drilling have improved the overall profitability of oil shale plays by enhancing the matrix -wellbore connectivity. The combination of these technologies has becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 9 publications
0
56
0
Order By: Relevance
“…The CT scan method is considered to be a nondestructive method to measure the cores' porosity, gas or oil saturation, and lithology characteristics within the cores (Siddiqui and Khamees, 2004;. The CT scan method has been widely used in petroleum engineering applications for describing the core porosity (Siddiqui et al, 2005), relative permeability (MacAllister et al, 1993), investigating the performance during core flooding experiments (London, et al, 2014), or other EOR processes (Kovscek et al, 2008;Simjoo et al, 2013;Tovar et al, 2014;. For this study, core plugs were scanned during the huff-n-puff tests to reflect the gas or oil saturation changes inside the core, and to help calculate the oil recovery in different stages.…”
Section: Introductionmentioning
confidence: 99%
“…The CT scan method is considered to be a nondestructive method to measure the cores' porosity, gas or oil saturation, and lithology characteristics within the cores (Siddiqui and Khamees, 2004;. The CT scan method has been widely used in petroleum engineering applications for describing the core porosity (Siddiqui et al, 2005), relative permeability (MacAllister et al, 1993), investigating the performance during core flooding experiments (London, et al, 2014), or other EOR processes (Kovscek et al, 2008;Simjoo et al, 2013;Tovar et al, 2014;. For this study, core plugs were scanned during the huff-n-puff tests to reflect the gas or oil saturation changes inside the core, and to help calculate the oil recovery in different stages.…”
Section: Introductionmentioning
confidence: 99%
“…Gamadi et al firstly did an experimental study on nitrogen huff and puff injection in shale oil rocks, and results showed a high oil recovery factor. Similar huff and puff experiments were carried out using CO 2 as the injection gas and showed good oil recovery factor in shale cores . Wan et al firstly simulated huff and puff gas injection in a hydraulic fractured shale reservoir using black oil models, and the results showed the oil recovery was improved to 29% by huff and puff gas injection compared with the primary recovery 6.5% from primary depletion.…”
Section: Introductionmentioning
confidence: 91%
“…Experimental results have exhibited that diffusion of injected gas into unconventional oil reservoirs is possible, but difficult to estimate (Vega et al, 2010;Hawthorne et al, 2013;Tovar et al, 2014). Furthermore, gas-into-liquid diffusion is much slower than gas-intogas diffusion.…”
Section: Diffusion -Fick's Lawmentioning
confidence: 99%